2019
DOI: 10.1021/acsmedchemlett.8b00590
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Drug Residence Time by Shielding of Intra-Protein Hydrogen Bonds: A Case Study on CCR2 Antagonists

Abstract: The target residence time (RT) for a given ligand is one of the important parameters that have to be optimized during drug design. It is well established that shielding the receptor−ligand hydrogen bond (H-bond) interactions from water has been one of the factors in increasing ligand RT. Building on this foundation, here we report that shielding an intra-protein H-bond, which confers rigidity to the binding pocket and which is not directly involved in drug−receptor interactions, can strongly influence RT for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…B) suggests a rearrangement of the hydrogen bond network that led to changes in the residence time . This is supported by subsequent MD simulations, which show that the residence time for MK‐0812 and structurally related ligands is directly dependent on the shielding of the Y120 3.32 ‐ E291 7.39 H‐bond from the water .…”
Section: Comparison and Implications Of Ccr2 Structuresmentioning
confidence: 59%
“…B) suggests a rearrangement of the hydrogen bond network that led to changes in the residence time . This is supported by subsequent MD simulations, which show that the residence time for MK‐0812 and structurally related ligands is directly dependent on the shielding of the Y120 3.32 ‐ E291 7.39 H‐bond from the water .…”
Section: Comparison and Implications Of Ccr2 Structuresmentioning
confidence: 59%
“…Apart from the role of pulling the IgV domain back to nivolumab, the N-terminal loop may also increase the nivolumab residence time by shielding the IgV-nivolumab H-bonds from water. In previously reported studies, the relationship between long residence time and accessibility of water has been established ( Schmidtke et al, 2011 ; Magarkar et al, 2019 ). In this study, binding of the N-terminal loop with nivolumab can create an environment of lower dielectric constant around the BC loop, shielded from bulk solvent ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Schmidtke et al showed that shielding ligand-receptor hydrogen bonds from water can contribute to long ligand residence time [ 87 ]. Interestingly, Magarkar et al recently found, based on MD simulations, that shielding of water from intra-protein interactions, not directly involved in ligand−receptor interactions, is also a relevant factor in ligand binding kinetics, as such interactions confer the rigidity of the binding site [ 88 ]. This opened new opportunities for the optimization of the residence time during drug development pipelines.…”
Section: Complementing Static Datamentioning
confidence: 99%